Higher Order Thinking Skills in Reading Literacy Questions at Vocational High Schools in Indonesia - Mukhlis, Muhammad; Suwandi, Sarwiji; Rohmadi, Muhammad; Setiawan, Budhi (Universitas Negeri Makassar, 2023)
This research is motivated by the demands of every student to have high-level thinking skills or known as HOTS. This ability can be known if the instrument used is classified as a question that requires high-level thinking skills. The purpose of this study was to analyze the fulfillment and percentage of indicators of high-level thinking skills in the minimum competency assessment of reading literacy at SMK Negeri Pekanbaru city. This research is qualitative research using a content analysis method. Data were collected using documentation techniques in the form of reading literacy questions obtained from teachers of Vocational High Schools throughout Pekanbaru City. The results showed that the AKM instrument was reading literacy with 79% HOTS category and 21% non-HOTS questions. In general, the question instructions have led to HOTS questions. The instrument contains dimensions that measure critical thinking, problem-solving, and creative thinking skills. Another thing that needs to be considered is how the instruments used can be developed using standardized instrument development steps so that the expected results can be recognized as true